2022
DOI: 10.1177/17455057221092266
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infectionand related factors among pregnant women at Debre Tabor General Hospital, Northwest Ethiopia, 2021:Anemia highly related with H. pylori

Abstract: Introduction: Infection with Helicobacter pylori is one of the most frequent chronic bacterial illnesses in humans. Pregnant mothers are the populations most vulnerable to H. pylori infection. The objective of this study was to assess the prevalence of H. pylori infection and associated factors among pregnant mothers having antenatal care at Debre Tabor General Hospital, Debre Tabor, Ethiopia, 2021. Methods and materials: Institutional based cross-sectional study design was conducted on 290 pregnant women. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Another study (18) showed a serum anti-H. pylori IgG antibody by ELISA > 1.1 was associated with hyperemesis gravidarum at a sensitivity of 86.67%, and a specificity of 65.91%.…”
Section: The Mean Level Of Anti-h Pylori Cag a Antibody In Sera Of Pr...mentioning
confidence: 97%
See 1 more Smart Citation
“…Another study (18) showed a serum anti-H. pylori IgG antibody by ELISA > 1.1 was associated with hyperemesis gravidarum at a sensitivity of 86.67%, and a specificity of 65.91%.…”
Section: The Mean Level Of Anti-h Pylori Cag a Antibody In Sera Of Pr...mentioning
confidence: 97%
“…The study included one hundred women during the first trimester of pregnancy from ALAlawia Teaching Hospital for Maternity in Iraq during the period from October 2021 until March 2022. Ages of total pregnancy ranged from (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years. Total patients were divided into four groups as follows: Group one: Included 25 pregnant with severe vomiting.…”
Section: Studied Subject Samplesmentioning
confidence: 99%
“…Previous studies have reported that nausea and vomiting of pregnancy (NVP), hyperemesis gravidarum(HG), FD, and some gastrointestinal symptoms are related to H. pylori infection. [3][4][5] However, few studies have shown that H. pylori infection increases the risk of these comorbidities and gastrointestinal symptoms and is associated with adverse pregnancy outcomes. [3][4][5][6] The current guidelines have not recommended routine H. pylori detection for pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, few studies have shown that H. pylori infection increases the risk of these comorbidities and gastrointestinal symptoms and is associated with adverse pregnancy outcomes. [3][4][5][6] The current guidelines have not recommended routine H. pylori detection for pregnant women. Our study retrospectively analyzed the data of 503 pregnant women from three large tertiary hospitals of China.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing several diagnostic approaches increases the detection of Hp-I. 2 Specifically, despite the advantages (easy to perform and rapid for Hp detection), SATs display several disadvantages. Because the principle of SAT is an antigen-antibody reaction, differences in antigens used for SAT in different geographic regions may cause heterogeneity of results; the diagnostic performances of different SATs are heterogeneous, and this could relate to the designs of the test like enzyme immunoassay and immunochromatographic assay (ICA) and for the selection of antibody, such as monoclonal antibody and polyclonal antibody.…”
mentioning
confidence: 99%